Предмет:
Другие предметыАвтор:
анонимРешим систему уравнений:
{ y - х = 20;
2 * х - 15 * у = -1;
{ y = 20 + x;
2 * х - 15 * у = -1;
Подставим y = 20 + x во второе уравнение и тогда получим:
{ y = 20 + x;
2 * х - 15 * (20 + х) = -1;
{ y = 20 + x;
2 * х - 15 * 20 - 15 * х = -1;
{ y = 20 + x;
2 * х - 300 - 15 * х = -1;
{ y = 20 + x;
-13 * х = -1 + 300;
{ y = 20 + x;
-13 * х = 299;
{ y = 20 + x;
х = -299/13;
{ y = 20 + x;
х = -23;
{ y = 20 + (-23);
х = -23;
{ y = 20 - 23;
х = -23;
{ y = -3;
х = -23;
Ответ: (-23; -3).
Автор:
hugo3qszДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть